The reinforcement attributes of multi-scale hybrid fiber throughout the uniaxial compression of ultra-low-weight foamed cement-based composites. (10th May 2020) - Yang, Yuanyi; Zhou, Qi; Deng, Yi
Highlights: The multi-scale fiber reinforcement was achieved while not increasing the density. Fiber hybridization contributed in three distinctive compressive progressions. A continuous constitutive damage model for foamed composites was proposed. Fiber reinforced foamed cement were dominated by the strain-softening behavior. Abstract: A comprehensive experimental investigation of multi-scale fiber-reinforced ultra-low-weight foamed cement-based composites throughout the quasi-static uniaxial compression was presented in this work. The multi-scale hybrid fibers combinations have achieved 133% and 116% increment in compressive strength and specific strength, which were contributed to a comprehensive reinforcement in different compressive stages. This multi-scale fibers combination was deemed as desirable reinforcing elements to supplement each other. Based on a continuous constitutive damage model, the strain-softening behavior of the fiber-reinforced samples in compression was elucidated. This study has provided substantial supporting evidence for practical analysis and numerical simulation in fiber-reinforced cellular materials.